Ring-opening and ring-expansion reactions of carborane-fused borirane. Issue 39 (16th September 2021) - Wang, Hanqiang; Zhang, Jie; Xie, Zuowei
Abstract : Carborane-fused borirane can not only engage in ring-opening reactions with different types of Lewis acids, but also undergo ring-expansion reactions with unsaturated molecules such as PhCHO, CO2 and PhCN to give five-membered boracycles. Abstract : Though the reaction chemistry of three-membered ring molecules such as cyclopropanes and their heteroatom-containing analogues has been extensively studied, the chemical properties of their boron analogues, boriranes, are little known thus far. This work describes the diverse reactivity patterns of carborane-fused borirane 2 . This borirane engages in ring-opening reactions with different types of Lewis acids, such as BBr3, GeCl2, GaCl3, BH3 (SMe2 ) and HBpin, affording a series of ring-opening products, in which M–X or B–H bonds add across the B–C(cage) bond of the three-membered ring in 2 . On the other hand, borirane 2 can undergo ring-expansion reactions with unsaturated molecules such as PhCHO, CO2 and PhCN to give ring-expansion products, five-membered boracycles, via a concerted reaction mechanism as supported by DFT calculations. The results of this work not only enrich the reaction chemistry of boriranes, but also offer new routes to boron-containing compounds and heterocycles.